2020
DOI: 10.1055/s-0040-1701292
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Fluoride Release and Antimicrobial Analysis of Commercial and Experimental Bioactive Glass/Nano-Oxide-Based Dentifrices

Abstract: Objectives The objectives were to measure fluoride release and assess the antimicrobial behavior of fluoride-doped nano bioactive glass (F-nBG) and nano zinc oxide (ZnO)-enriched novel dentifrices. Materials and Methods Experimental dentifrices were synthesized by incorporating ZnO nanoparticles and F-nBG (1.5 wt% and 4 wt%) as active ingredients. The fluoride release behavior of suspensions and elutes of samples were analyzed by ion selective electrode. Antimicrobial activity and minimum bactericidal concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…In addition, F incorporation into phosphate-based glass could inhibit the growth of periodontal pathogens, such as Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis (Liu et al 2016). Compared with F-doped silica-based glass alone, the combination of F-doped silica-based glass and ZnO can effectively reduce S. mutans growth (Gul et al 2020). We demonstrated that Zn- and F-releasing phosphate-based glasses exerted robust antimicrobial effects against S. mutans , one of the main biofilm-forming bacterial species in the oral cavity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, F incorporation into phosphate-based glass could inhibit the growth of periodontal pathogens, such as Aggregatibacter actinomycetemcomitans and Porphyromonas gingivalis (Liu et al 2016). Compared with F-doped silica-based glass alone, the combination of F-doped silica-based glass and ZnO can effectively reduce S. mutans growth (Gul et al 2020). We demonstrated that Zn- and F-releasing phosphate-based glasses exerted robust antimicrobial effects against S. mutans , one of the main biofilm-forming bacterial species in the oral cavity (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, fluoride release was found to be more efficient from suspensions than from elutes of the samples of the dentifrice. This is suggested to be of great clinical significance since dentifrices are used in the suspension form during brushing [ 160 ].…”
Section: Zincmentioning
confidence: 99%